ANALYSIS OF HANDLING SPORT INJURY IN ATHLETES PENCAK SILAT (CASE STUDY IN SPORT CLINIC RSUD DR. SOETOMO SURABAYA IN 2016) - Susilo, Rahmat Dwi (Jurnal Kesehatan Olahraga, 2018)
Pencak Silat is one of the sports played and studied by the community, Pencak Silat is also one of the sports that is learned for the purpose of self defense from unfavorable circumstances. Pencak Silat is one of the sport is hard so that during practice or match not infrequently will occur because of injury to the anatomical arrangement outside the normal pressure will result in injury. This study aims to (1) Know what sports injuries experienced by martial arts athletes. (2) To know how the handling of sports sports injuries on athletes of martial arts at Sport Clinic RSUD dr. Soetomo Surabaya. This type of research is descriptive qualitative because it describes about the handling of sports injuries at the martial art athletes ever handled in sports clinic RSUD dr. Soetomo Surabaya in 2016 that is as many as 4 athletes and only 3 who can be interviewed. Results obtained from interviews to 3 athletes namely: 1 athlete suffered a Susp injury. Triangular Fibrocartilage Complex Tear D. (wrist injury) after being examined by a team of doctors using a usg device known to have injuries to the wrist is recommended for surgery but not performed and only treatment to accelerate cell regeneration and reduce the intensity of injured hands and takes time for 6 months to recover. In athletes 2 who suffered injuries Microfracture Cruris D 1/3 (fracture on the shin) at the initial examination of the team of doctors do rontgen not known injury, after the examination with MRI is known to have a fine fracture injury on the shin after it was given the handling sorted using the tool and given a jel and advised not to run and jump, athlete 2 takes 2 months to heal. While on athletes 3 who suffered injury Anterior Talo Fibular Ligament and Posterior Tibial Tendon Dysfunction S (injury to the ankle) when examined with usg and rontgen not yet known what injury by the team doctor after performing an MRI examination is known to have double injury on the ankle and performed action surgery and following laser and tens therapy and is recommended to rest for 1 year. At the time the researchers conducted interviews athletes 3 still not healed and predicted by the doctor recovered after 1 year with a record of doing therapy regularly. Keywords : Injuries, Pencak Silat, Sport Clinic